Therapeutic Communication in Schizophrenic Patients: A Systematic Literature Review - Nompo, Rifki Sakinah (Scientia Psychiatrica, 2023)
Introduction: Schizophrenia is a complex mental disorder that affects an individual's thoughts, perceptions, and behaviors. Therapeutic communication in schizophrenic patients refers to the communication approach used by health professionals or therapists to interact with schizophrenic patients with the aim of assisting them in recovery and improving their quality of life. This study aimed to explore forms of therapeutic communication that could be used to improve improvements in schizophrenia patients. Methods: The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding therapeutic communication and schizophrenia. The search was performed using the terms "therapeutic communication" OR "psychoeducation" OR "psychotherapy" AND "schizophrenia”. Results: Among all studies included in the review, there were three qualitative studies and one observational study. In addition, the study did not provide information on whether there were deviations from the intervention data, bias in measuring outcomes, and bias in the selection of reported outcomes. Conclusion: Therapeutic communication can be adapted to the individual needs of schizophrenic patients. To build a strong therapeutic alliance, open conversation, trust, and respect play a fundamental role, with the ultimate goal of building a partnership to optimize patient outcomes.